Identification of a Novel MYH9 Mutation in a Young Adult With Inherited Thrombocytopenia and Recurrent Seizures by Targeted Exome Sequencing. Issue 3 (April 2020) - Yang, Eu Jeen; Park, Kyung Mi; Kim, Yoo-Mi; Jung, Ki Sun; Lim, Young Tak; Cheon, Chong Kun
Abstract : May-Hegglin anomaly (MHA) is a rare autosomal dominant disorder caused by a mutation in the myosin heavy chain 9 ( MYH9 ) gene. MHA patients have variable clinical manifestations including thrombocytopenia, renal injury, hearing impairment, and cataracts. We describe a 25-year-old man with isolated thrombocytopenia initially. He experienced recurrent seizures with stable thrombocytopenia after the first seizures related to intracranial hemorrhage. He was identified a novel c.3452C>T mutation by targeted exome sequencing. If a patient with thrombocytopenia shows recurrent seizures as well as renal, hearing, visual symptoms, MHA should be suspected and the targeted exome sequencing is considered an effective diagnostic tool.